Plenary Conference 4: Impact of The Use of Vegetation in Urban Environments: Green Roofs and Walls - Viecco Márquez, Margareth (Revista Productos Naturales, 2022)
Anthropogenic activities have generated multiple negative environmental impacts, placing human health and the environment at risk...